Measuring nonresponse cross-nationally - Annelies G. Blom (University of Essex, Institute for Social and Economic Research (ISER), 2008)
This paper investigates the measurement of nonresponse outcomes across countries. It consists of three sections. Section one proposes a conceptual framework of influences on the response outcomes available for analysis. Section two develops a crossnational codeframe of response outcome codes. The last section investigates the impact that differential ways of deriving final case outcomes have on the estimated response, contact and cooperation rates. The results emphasise the importance of careful measurement of the nonresponse process for conclusions about the similarity and differences across countries in processes leading to nonresponse.
Keywords: 330